Cartographies of youth resistance hip-hop, punk, and urban autonomy in Mexico - Magaña, Maurice Rafael, 1979- (University of California Press, 2020)
"In his exciting new book, based on a decade of ethnographic fieldwork, Maurice Magaña considers how urban and migrant youth in Oaxaca embrace subcultures, from hip-hop to punk, and adopt creative organizing practices to create meaningful channels of participation in local social and political life. In the process, young people remake urban space and construct new identities in ways that directly challenge elite visions of their city and essentialist notions of what it means to be Indigenous in the contemporary era. Cartographies of Youth Resistance is essential reading for students and scholars interested in youth politics and culture in Mexico, social movements, urban studies, and migration"--